Autonomy, Motivation, and Knowledge as Catalysts for Innovation in Nepalese Banking - Chhetri, Ashmita Dahal; Khanal, Anupama (Jana Adarsha Research Journal, 2026)
The research paper will explore how autonomy, intrinsic motivation, diversity of knowledge, and individual absorptive capacity (IAC) encourage the behavior of innovative work (IWB) among employees in Nepal banking industry. Based on a micro-foundational view on absorptive capacity, we conceptualize individual absorptive capacity (IAC) in terms of two aspects, including Potential Absorptive Capacity (PAC-ind) and Realized Absorptive Capacity (RAC-ind) and suggest Autonomy at Work (AW) as a modifying variable. The data related to the above scales is gathered through a survey by means of validated, translated/back-translated scales of IAC, Diversity of Prior Knowledge (DPK: education, work experience, life experience), Intrinsic Motivation (IM), IWB, and AW. The instrument was reviewed by experts, piloted and common method bias checks. The responses obtained among the managers employed in commercial banking organizations were analyzed using PLS-SEM (SmartPLS), which measured reliability, convergent/discriminate validity, and structural correlation. The findings indicate that six out of nine hypotheses were accepted. PAC-ind RAC-ind had a positive and significant correlation, and RAC-ind IWB effect was strong, which means that innovation is achieved by the transformation and implementation of knowledge and not by its acquisition. The enhancement of PAC-ind by DPK was positive, whereas it was not enhancing RAC-ind or IWB, which supports the necessity of structured learning processes. IM even increased PAC-ind and not RAC-ind indicating that motivation starts learning and needs facilitating conditions to be applied. AW enhanced IM and greatly empowered the RAC-ind → IWB direction (moderation), highlighting empowerment as the step towards transforming applied knowledge into innovation. In general, the results place IAC with the help of autonomy and motivation in the core of developing the employee-led innovation in Nepalese banks, and provide practical recommendations to HR policies regarding the role of empowerment, learning, and management of innovation.